Factors related with nursing students’ health literacy: a cross sectional study - Ramón-Arbués, Enrique; Granada-López, José Manuel; Antón-Solanas, Isabel; Cobos-Rincón, Ana; Rodríguez-Calvo, Antonio; Gea-Caballero, Vicente; Tejada-Garrido, Clara Isabel; Juárez-Vela, Raúl; Echániz-Serrano, Emmanuel (Frontiers in Public Health, 2023)
Background Nursing professionals have a crucial role in promoting health literacy in health services, so it is necessary to ensure health literacy skills in future health professionals. Objective The objective of the study was to examine the health literacy of nursing students and its associated factors. Methods A cross-sectional descriptive study was carried out on 460 nursing students. For data collection, a semi-structured questionnaire was obtained on sociodemographic characteristics, perception and health care, use of the health system and lifestyles. In addition, health literacy was assessed using the European Health Literacy Questionnaire. Results 6.1% of the participants had an inadequate level of health literacy and 36.5% problematic. The probability of having sufficient health literacy is directly associated with age; and inversely with smoking, prolonged screen time and living alone (p < 0.05). Conclusion A large percentage of nursing students need to improve their health literacy skills. It is necessary to integrate a greater number of contents in health literacy in the curriculum of nursing students.